Historiografi Pesantren di Indonesia - Sudarmo, Fatiyah (Historia Madania: Jurnal Ilmu Sejarah, 2021)
Â  The aim of this research is to describe and analyze the historiography writing style of pesantren in Indonesia. The pesantren has historically been a â€œgenuineâ€ model of the Islamic education system in the archipelago. At the beginning of its establishment and development, pesantren is a form of education and learning of Islamic religion (recitation assemblies) which is managed by a kiai. At this stage, the pesantren has the main elements, namely: kiai, mosques, and santri. We know this type from the name of pesantren salafiyah. Then it develops according to the times and knowledge in terms of management and learning systems as well as the knowledge being taught to develop by incorporating general knowledge, which became known as "khalaf" pesantren. Then there is another one, namely a combination of the two, between salafiyah and khalaf. The themes of writing the history of pesantren in Indonesia are various. First, the theme of the pesantren development. Second, the study of figures or biographies of the kiai. Third, the dynamics of pesantren with the social conditions of the community. Fourth, the pesantren education system. The writing of pesantren historiography in Indonesia is the story of pesantren, so all writings can be categorized into three forms: traditional, colonial and modern historiography. Â  Keywords: historiography, pesantren, methodology.